The Municipal Historical Archive of Abanilla background and current organization - Albentosa Aja, Juan Luis; Saurín Martínez, Daniel (Revista General de Información y Documentación, 2024)
This work aims to find out the origins of the Historical Local Archive of Abanilla (HLAA), as well as the approach, concern and involvement of the Local Council of the village in relation to the keeping and custody of the papers it was producing and receiving through the Modern and Contemporary eras, and, as high point, to show the researcher community archival tasks that have been carried out during the year 2023 by qualified crew hired by the City Council of Abanilla. In order to see through the objectives proposed, documents kept in both Local and Regional archives of Murcia have been studied, referred in the HLAA itself and the National Historical Archive (NHA), which has allowed to know different inventories that the Local Council had them done from the XVI century to the XX, actions undertaken in order to assure the safeguarding of papers placed in both the archive and a chest during these centuries, and archival tasks and the classification picture made by external technical members, in which we can observe the existance of Council documents themselves and from other higher institutions, as well as notarial, ecclesiastic and civil.